Temperature sensitivity modulation through changing the vanadium concentration in a La2MgTiO6:V5+, Cr3+ double perovskite optical thermometer. Issue 28 (1st July 2021) - Stefańska, Dagmara; Bondzior, Bartosz; Vu, Thi Hong Quan; Grodzicki, Miłosz; Dereń, Przemysław J.
Abstract : To fulfil the requirements of operating at low temperature in a harsh environment, the investigation on optical thermometers plays an increasingly important role. Abstract : To fulfil the requirements of operating at low temperature in a harsh environment, the investigation on optical thermometers plays an increasingly important role. In this work, the influence of vanadium concentration on the capability of temperature readout by La2 MgTiO6 :V 5+, Cr 3+ luminescent thermometers was investigated for the first time. The presence of V 3+ and V 5+ was verified by XPS and absorption measurements. In the emission spectra, a blue–green emission region was assigned to both host and V 5+ emission. Moreover, a spin-forbidden emission of Cr 3+ ions was also detected. Vanadium ions in the +3 oxidation state do not exhibit luminescence, but play a role as a charge compensator. The highest emission intensity was obtained from the sample doped with 0.1% V. Besides, with increasing vanadium concentration, a redshift in the maximum position of the spectrum was observed corresponding to a movement from the greenish blue to yellowish green region in the CIE1931. It was shown that the relative sensitivity ( S r ) and the temperature operating range can be easily modified by changing the concentration of vanadium ions. In particular, the outstanding relative sensitivities of 1.71% K −1 (at 187 K) and 1.96% K −1 (at 165 K) obtained from La2 MgTiO6 :0.1%V 5+, Cr 3+ and La2 MgTiO6 :0.05%V 5+, Cr 3+ demonstrated the enormous potential of this material for thermal sensing application.